You are on page 1of 5

7.5.

PROBLEMS

93

7.5

Problems

6.3.2 Let X be a random variable with range [1, 1] and density function fX . Find (X ) and 2 (X ) if fX (x) = 0 for |x| > 1, and for |x| 1 Since the interval [1, 1] is symmetric about x = 0, any even density (f (x) = f (x)) will have = 0. Problem (a) is one. 3 (a) fX (x) = (1 x2 ), 4 = 3 x2 x4 3 x (1 x2 ) dx = [ ] 4 2 4 1 4
1 1 1 1

= 0.
1 1

E (X 2 ) =

3 3 x3 x5 x2 (1 x2 ) dx = [ ] 4 4 3 5 1 1 2 = E (X 2 ) 2 = . 5

1 5

Since fX

cos(x/2), 4 is even, = 0, and 2 = E (X 2 ). (b) fX (x) =


1

2 =
1

x2
1

cos(x/2) dx 4
1

22 [x sin(x/2) 4

1 1

2 2x sin(x/2) dx] 1
1

2 = 1 + x cos(x/2)

2 cos(x/2) dx]

=1

8 2

x+1 , 2 1 x2 x3 x+1 dx = + = x 2 4 6 1 (c) fX (x) =


1

1 1

2 = . 6
1 1

E (X 2 ) =
1

x2

x3 x4 x+1 dx = + 2 6 8

2 = . 6

94

CHAPTER 7. EXPECTED VALUE AND VARIANCE 2 = E (X 2 ) 2 = 1 1 2 = . 3 9 9

3 (d) fX (x) = (x + 1)2 . 8 = 3 8 3 8


1

x(x2 + 2x + 1) dx =
1 1

34 1 = . 83 2 3 16 2 = . 8 15 5

E (X 2 ) =

x2 (x2 + 2x + 1) dx =
1

2 1 3 = . 5 4 20 6.3.3 The lifetime in hours of the ACME light bulb is a random variable T with density function 2 = E (X 2 ) 2 = fT (t) = 2 tet , = .05.

What are the expected value and variance for the lifetime? After integration by parts,

=
0

tfT (t) dt =
0

t exp(t) dt = 2
0

2 2

exp(t) dt = 2/.

Similarly, E (T ) =
0 2

2 t3 exp(t) dt = 6/2 ,

so 2 = E (T 2 ) 2 = 2/2. With = .05 we get = 40, 2 = 800. 6.3.6 Let T be a random variable with density fT (t) and range [0, ]. Find (T ) and 2 (T ) if fT (t) = 0 for t < 0, and for t 0 (a) fT (t) = 3e3t , This is just an exponential density with = 3, so integration by parts gives mu = 1/ = 1/3, 2 = 1/ 9 .

7.5. PROBLEMS

95

9t 3t e , 2 I think the factor two is an error. This should be (b) fT (t) = (b) fT (t) = 9te3t , making it a case of problem 6.3.3 with = 3. Thus = 2/ 3 , 2 = 2/ 9 . 3 . (1 + t)4
0

(c) fT (t) = In this case integration by parts gives

=
0

3 t dt = (1 + t)4
2

1 1 dt = , 3 (1 + t) 2
0

E (T ) =
0

3 dt = t (1 + t)4

1 dt = 1, (1 + t)2

so = 1/ 2 , 2 = E (T 2 ) 2 = 3 / 4 . 6.3.7 Let X be a random variable with density fX (x). Show that the function (a) = E ([X a]2 ), takes its minimum value when a = (X ), and in that case (a) = 2 (X ). We have

(a) = E ([X a]2 ) =

(x a)2 fX (x) dx =

(x2 2ax + a2 )fX (x) dx.

This is a quadratic polynomial in a, and has its minimum when (a) = 0. Writing this equation we nd

0 = 2

xfX (x) dx + 2a

fX (x) dx,

or (X ) =

xfX (x) dx = a

fX (x) dx = a.

96

CHAPTER 7. EXPECTED VALUE AND VARIANCE

Of course by the denition of the variance 2 (X ) = (X ) = E ([X a]2 ). 6.3.17 Let X and Y be random variables. The covariance Cov (X, Y ) is dened by cov (X, Y ) = E ([X (X )][Y (Y )]). (a) Show that cov (X, Y ) = E (XY ) E (X )E (Y ). By linearity of the expected value, cov (X, Y ) = E ([X (X )][Y (Y )]) = E (XY ) (Y )E (X ) (X )E (Y ) + (X )(Y ) = E (XY ) E (X )E (Y ). (b) Using (a), show that cov (X, Y ) 0 if X and Y are independent. If X and Y are independent then E (XY ) = E (X )E (Y ), so cov (X, Y ) = E (XY ) E (X )E (Y ) = 0. (c) Show that V (X + Y ) = V (X ) + V (Y ) + 2cov (X, Y ). Using the denition, V (X + Y ) = E ([X + Y (X ) (Y )]2 ) = E ([(X (X ) + (Y (Y ))]2 ) = E ([X (X )]2 ) + 2E ([X (X )][Y (Y )]) + E ([Y (Y )]2 ) = V (X ) + V (Y ) + 2cov (X, Y ). 6.3.18 Let X and Y be random variable with positive variance. The correlation of X and Y is dened as (X, Y ) = (a) Using 17(c), show that 0V( X Y + ) = 2(1 + (X, Y )). (X ) (Y ) cov (X, Y ) . V (X )V (Y )

The variance of any random variable is nonnegative. First, cov ( X Y X (X ) Y (Y ) , ) = E ([ ][ ]) (X ) (Y ) (X ) (X ) (Y ) (Y )

7.5. PROBLEMS = E( so by 17 (c), V( X Y X Y X Y + )=V( )+V( ) + 2cov ( , ) (X ) (Y ) (X ) (Y ) (X ) (Y ) = V (Y ) XY (X ) (Y ) V (X ) + + 2 E ( ) 2 2 (X ) 2 (Y ) (X ) (Y ) (X ) (Y ) =2+2 (b) Now show that 0 V( X Y ) = 2(1 (X, Y )). (X ) (Y ) E (XY ) (X )(Y ) = 2(1 + (X, Y )). V (X )V (Y ) XY (X ) (Y ) ) (X ) (Y ) (X ) (Y )

97

Use the result of (a) with X and Z = Y , noting that cov (X, Y ) = cov (X, Y ). (c) Show that 1 (X, Y ) 1. From (a) and (b) we get 0 (1 + (X, Y ))(1 (X, Y )) = 1 (X, Y )2 , or (X, Y )2 1, which is equivalent to 1 (X, Y ) 1.